Student political involvement in the 13th Malaysian General Election: A case study among students of public university in Klang Valley - Ab Khalid, Nur Afzan; Badaruddin, Shaharuddin (2014)
Student and politic, this topic has been much debated for some time and there are many different views and thoughts on whether student should be allowed to take part in politics or not. Student political involvement is related with Student Movement.Student Movement has played a crucial role in many major social and political transformations.The purpose of this study is to analyze the student political involvement in the 13th Malaysian General Election.The development of student activism in Malaysia political landscape after the amendment of Universities and College Universities Act 1971.In addition, the researcher goal is to identify the factors contributing to student involvement in politics and general election.And how student political involvement gives impact to the social development in Malaysia.Moreover, how these involvement of students can affect the political future and social issues in the short term and long-term perspectives.